Vadba hoje na tekočem traku in lokomatu pri pacientih z nepopolno okvaro hrbtenjače - Špoljar, Janez (Rehabilitacija (Ljubljana), 2014)
Background: Treadmill training in patients with incomplete spinal cord injury is based on research and evidence about existence of central pattern generators within the spinal cord. This approach is one of the established approaches in rehabilitation and has been a part of everyday practice for many years. Training is time-limited because of inconvenient ergonomic position of the physiotherapists and their fatigue. Besides, it does not enable patients to learn an optimal gait pattern. That is why development of medical devices for robotic gait training has taken place all over the world. Lokomat is the most common one. Methods: We gathered the data about patients who were included in the therapy with the Lokomat from November 2010 to December 2013 at the University Rehabilitation Institute in Ljubljana: data about the number of included patients, gender, age, cause of injury, injury consequences, time from injury onset to inclusion in the therapy, total number of training sessions, average number of training sessions per patient, average body-weight support during therapy, average duration of a training session and average gait velocity. Data about the number of physiotherapists needed for therapy, gait velocity, body weight support and duration of training sessions were compared to the data gathered from assisted treadmill training. The latter were gathered from the literature. Results: Fourty-three males (average age 54 years) and six females (average age 58 years) with spinal cord injury were included in the treatment with the Lokomat. Three fourths of the patients were included in the treatment within the first year after injury. In total they had 805 training sessions, 16.4 sessions per hospitalised patient on average. The training session lasted for 30.3 minutes on average. The average body weight support was 31.1 kilograms; the average gait velocity was 1.5 km/h. In the studies of assisted treadmill training two to three physiotherapists were needed for the therapy, gait velocity was 0.19 m/s to 0.54 m/s, body weight support ranged from 30 % to more than 60 %, training duration was between 20 and 45 minutes. Conclusions: The comparison between the approaches shows advantages of the Lokomat in terms of fewer physiotherapists needed for the therapy, higher gait velocity and longer duration of training units.
Keywords: fizioterapija; Gait; hoja; Physical Therapy Modalities; physiotherapy; poškodbe hrbtenjače; rehabilitacija; Rehabilitation; Robotics; robotika; Spinal Cord Injuries; vocational rehabilitation